2017
DOI: 10.1038/s41598-017-11818-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and antioxidant activity of the essential oils of Citrus sinensis and Citrus latifolia

Abstract: The essential oils of Citrus sinensis and Citrus latifolia showed antimycotic activity against Candida spp. isolated from the oral cavity; they are neither mutagenic on the Ames test nor cytotoxic. Their main components are R-(+)-limonene, β-thujene, α-myrcene and γ-terpinene. The aim of this work was to evaluate their antimutagenic and antioxidant capacities. Antimutagenic properties were evaluated against MNNG and ENNG on S. typhimurium TA100; against 2AA on strain TA98 and in front of 4NQO and NOR on strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 31 publications
0
31
1
1
Order By: Relevance
“…In the current study, a significant augmentation of the hepatic LPO content of tambaqui fed 2.0 ml EOCL/kg diet was observed, indicating the occurrence of lipid damage, which is contrast to the study by Toscano‐Garibay et al.,(2017), who reported that EOCL (200 µl) in vitro presented potent antioxidant capacity through the reduction of lipid damage in cells. It is important to emphasis that alterations in the antioxidant/oxidant status can be dose‐dependent, since the lower EOCL concentrations did not alter LPO content of tambaqui liver and muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, a significant augmentation of the hepatic LPO content of tambaqui fed 2.0 ml EOCL/kg diet was observed, indicating the occurrence of lipid damage, which is contrast to the study by Toscano‐Garibay et al.,(2017), who reported that EOCL (200 µl) in vitro presented potent antioxidant capacity through the reduction of lipid damage in cells. It is important to emphasis that alterations in the antioxidant/oxidant status can be dose‐dependent, since the lower EOCL concentrations did not alter LPO content of tambaqui liver and muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, natural products present in medicinal plants like EOs shows significant antioxidants performance from different plant source. The EOs obtained from Zanthoxylum alatum, Ammodaucus leucotrichus, Marrubium globosum, Citrus sinensis and Citrus latifolia, Lawsonia inermis, Thymus fontanesii, Artemisia herba-alba and Rosmarinus officinalis, Syzygium aromaticum L., Origanum vulgare L., Mentha spicata L., and Eremanthus erythropappus M showed promising antioxidant activity [132][133][134][135][136][137].…”
Section: Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
“…Means in the same row with different superscripts differ (p < 0.05). 1 CON: basal diet; 2 ANTI: CON + 75 g/t chlortetracycline; 3 CE: CON + 300 mL/t citrus extract; 4 SEM means standard error of the mean; 5 EAA: essential amino acids; 6 NEAA: non-essential amino acids; 7 ΣEAA = Total essential amino acids; 8 ΣNEAA = Total non-essential amino acids; 9 ΣAA = Total amino acids.…”
Section: Pfaamentioning
confidence: 99%
“…Hesperidin, for example, can prevent intestinal inflammation in mice [4]. Citrus extract (CE) has various biological functions, including anti-cancer [5], anti-bacterial [6,7], anti-oxidant [7,8], and anti-inflammatory [9,10]. Its strong anti-oxidant and anti-inflammatory effects are especially valuable in improving animal health [9,11].…”
Section: Introductionmentioning
confidence: 99%